Effects of Metal Ions on H2 Generation during Photolysis of Suspended TiO2 in Aqueous Systems - Dey, G.R. (Journal of Applied Solution Chemistry and Modeling, 2015)
Nowadays, photocatalysis is being applied as a promising technique for decontamination, purification, deodorization, etc. of polluted air and wastewaters. This technique attempts also to generate renewable and non-polluting fuels utilizing various carbon and hydrogen sources. In this context, studies on photo-catalytic generation of H2 using 0.1% w/v TiO2 photo catalyst as a suspension in water was carried out using 350 nm light. This was explored further in presence of various metal ions such as Ag+, Cu2+, Fe2+, Au3+ and V5+ at different ambient such as air and CO2, in presence of a hole scavenger (2-propanol and formic acid). H2 yields in CO2-purged systems as analyzed in GC-TCD were reasonably higher, and increased further when metal ions were added into the systems. Based on H2 yields, HCOOH was found to be a more supportive hole scavenger as compared to 2-propanol in metal ions containing systems. Besides the formation of low to high concentrations of various gaseous products, nanoparticles of gold, silver and copper were also observed as photolysis products. This indicated that the presence of both reduced metal ions and their in-situ generated nanoparticles at various stages either in the free/unbound and/or associated with TiO2 photocatalyst in aqueous systems, together play a significant role in enhancing the H2 yields.